Mike Dill, D88, practices dentistry from his home office. Photo 187 - Ko, Melody (Tufts Archival Research Center, 2008)
Mike Dill, D88, practices dentistry from his home office. One of the benefits of working at home means that he does not have to be separated from his five children while at work.